ENHANCING FARMER GROUPS’ STRENGTH: HOW EFFECTIVE IS THAILAND’S PROJECT ON STRENGTHENING AGRICULTURAL PRODUCTION GROUPS? - Jansuwan, Para (PEOPLE: International Journal of Social Sciences, 2024)
In 2021, the Thai government implemented the project on strengthening agricultural production groups to enhance their operational strength through providing them with required supports. This study aimed to evaluate if the project contributes to improving the groups’ strength, the group members’ income and the application of knowledge gained in their households. Logic model was applied as this evaluation’s conceptual framework and a Propensity Score Matching method was applied to analyse the project’s impact. Data were collected from the project participants (265 people) and non-participants (241 people) through a survey in 12 provinces in four regions of Thailand. The results revealed that 53.50% and 28.12% of the group members reported that their group was the strongest and very strong, respectively. This is because most members (86.27%) provide assistance to each other and most (86.22%) cooperate in carrying out the groups’ activities. Participating group members who received land allocation from the Agricultural Land Reform Office earned an average of 28,482 baht more per year than non-participating members. Participating farmer housewife group members earned an average of 12,638 baht more per year than non-participating members. Participating farm youth was 24.19% more likely to apply the knowledge gained in their household than non-participating youth. In conclusion, the project was effective and should therefore be continuously extended its results. Its bottom-up approach should be applied to other projects with similar characteristics. In addition, budgets from various sources should be integrated to provide different farmer groups with more opportunities to participate in the future projects.